Evaluation of Contrast-Enhanced Intraoperative Ultrasound in the Detection and Management of Liver Lesions in Patients with Hepatocellular Carcinoma. (5th August 2019) - Pace, Cristina; Nardone, Vittorio; Roma, Silvia; Chegai, Fabrizio; Toti, Luca; Manzia, Tommaso Maria; Tisone, Giuseppe; Orlacchio, Antonio
Abstract : Aim . To evaluate the role of contrast-enhanced intraoperative ultrasound (CE-IOUS) during liver surgery in the detection and management of liver lesions in patients with hepatocellular carcinoma (HCC). Materials and Methods . From December 2016 to December 2017, 50 patients with HCC, who were candidates for liver resection, were evaluated with intraoperative ultrasound (IOUS). For all patients, MRI and/or CT were performed before surgery. During surgery, IOUS was performed after liver mobilization, and when nodules that had not been detected in the preoperative MRI and/or CT were observed, CE-IOUS scans were carried out with the dual purpose of better characterizing the unknown lesion and discovering new lesions. Results . In 12 patients, IOUS showed 14 nodules not detected by preoperative MRI and/or CT, before surgery. Out of the 12 lesions, five presented vascular features compatible with those of malignant HCC to the evaluation with CE-IOUS and four of these were simultaneously treated with intraoperative radiofrequency ablation (RFA). The fifth lesion was resected by the surgeon. The remaining nine lesions recognized by IOUS were evaluated as benign at CE-IOUS and considered regenerative nodules. The last diagnosis was confirmed during follow-up obtained by means of CT and/or MRI after 1, 3, 6, or 12 months. Conclusion . In our experience, CE-IOUS is a useful diagnostic tool in both benign pathologies, such as regenerative nodules, and malignant liver lesions. The advantage of this approach is the possibility of intraoperatively characterizing, based on vascularization patterns, lesions that could not be diagnosed by preoperative imaging, resulting in modification of the surgical therapy decision and expansion of the resection or intraoperative ablation.